Toxic Masculinity Represented in Collen Hoover’s It Ends With Us (2016) - Waruwu, Arni Kristin; Wahyuni, Delvy (English Language and Literature, 2023)
This study is an analysis of Colleen Hoover's novel, "It Ends with Us". Toxic masculinity refers to harmful social norms and expectations that promote traditional gender roles that associated with how man should behave to be called as being areal man. This research aims to find out what are the forms of toxic masculinity that represented by the male character in this novel. The result of this research showsthat there are three forms of toxic masculinity that can be found in this novel, namely misogyny, domination and violence.